Architectural Engineering Achieves High‐Performance Alloying Anodes for Lithium and Sodium Ion Batteries. Issue 19 (18th March 2021) - Guo, Songtao; Feng, Yuezhan; Wang, Libin; Jiang, Yingjun; Yu, Yan; Hu, Xianluo
Abstract: Tremendous efforts have been dedicated to the development of high‐performance electrochemical energy storage devices. The development of lithium‐ and sodium‐ion batteries (LIBs and SIBs) with high energy densities is urgently needed to meet the growing demands for portable electronic devices, electric vehicles, and large‐scale smart grids. Anode materials with high theoretical capacities that are based on alloying storage mechanisms are at the forefront of research geared towards high‐energy‐density LIBs or SIBs. However, they often suffer from severe pulverization and rapid capacity decay due to their huge volume change upon cycling. So far, a wide variety of advanced materials and electrode structures are developed to improve the long‐term cyclability of alloying‐type materials. This review provides fundamentals of anti‐pulverization and cutting‐edge concepts that aim to achieve high‐performance alloying anodes for LIBs/SIBs from the viewpoint of architectural engineering. The recent progress on the effective strategies of nanostructuring, incorporation of carbon, intermetallics design, and binder engineering is systematically summarized. After that, the relationship between architectural design and electrochemical performance as well as the related charge‐storage mechanisms is discussed. Finally, challenges and perspectives of alloying‐type anode materials for further development in LIB/SIB applications are proposed. Abstract : Architectural engineering plays an important role in high‐capacity alloying‐type anodes for lithium‐ and sodium‐ion batteries (LIBs/SIBs). This review focuses on the recent progress in effective structural strategies by nanostructuring, incorporation of carbon, intermetallics design, and binder engineering to achieve reversible alloying anodes. Moreover, challenges and perspectives of alloying anodes for next‐generation LIBs/SIBs with high energy densities are proposed.